2018
DOI: 10.1159/000494409
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection in Patients with Ulcerative Colitis

Abstract: Patients with ulcerative colitis have an increased risk of developing colorectal cancer. This risk has been estimated to reach about 7% at 20 years of disease, 7–14% at 25 years, and as high as 30% after 35 years. The guidelines for the management of inflammatory bowel disease recommend endoscopic resection of circumscribed dysplasia and ongoing colonoscopic surveillance as a reasonable strategy in patients with ulcerative colitis. Submucosal fibrosis due to background inflammation could hamper adequate liftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…When we undertake piecemeal resections during EMR, we carefully evaluate the stump of the ulcer, and additional mucosal cautery trimming is performed, where necessary, which may reduce the risk of local recurrence. While local recurrence (0%–22.2%) and R0 resection rates (77%–80%) have been reported following ESD of tumors in patients with UC, 9,11,12,21,30 our lower local recurrence rate corresponded with a higher R0 resection rate (97%) compared with those reported previously.…”
Section: Discussionsupporting
confidence: 43%
“…When we undertake piecemeal resections during EMR, we carefully evaluate the stump of the ulcer, and additional mucosal cautery trimming is performed, where necessary, which may reduce the risk of local recurrence. While local recurrence (0%–22.2%) and R0 resection rates (77%–80%) have been reported following ESD of tumors in patients with UC, 9,11,12,21,30 our lower local recurrence rate corresponded with a higher R0 resection rate (97%) compared with those reported previously.…”
Section: Discussionsupporting
confidence: 43%
“…Endoscopic resection, including ESD, is a therapeutic technique and is simultaneously an important diagnostic method for determining the need for a total excisional biopsy to investigate the histological diversity of the completely resected specimen. According to the responses to this questionnaire, ESD is recognized as a standard en bloc endoscopic method for UCAN . Japanese guidelines strongly recommend considering sporadic localized tumors in chronic inflammatory conditions such as UC as one of the indications for colorectal ESD .…”
Section: Questionnaire Survey On the Current Status Of Endoscopic Diamentioning
confidence: 99%
“…The ASGE practice guidelines recommend en bloc resection of raised, endoscopically visible, dysplastic lesions with distinct borders in regions of chronic active colitis that might be prone to fibrosis by EMR or ESD 4 . However, to date, the outcomes data on colorectal ESD for the management of IBD-associated dysplastic lesions are scarce and limited to studies from Asia and Europe 7 8 9 10 11 12 . In this US multicenter study on clinical outcomes of ESD in IBD, we found that ESD was associated with high en bloc (95.6 %) and R0 resection rates (75.5 %), with a median lesion size of 30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…ESD was performed as previously described ( Fig. 1 ) 7 8 . In brief, the procedures were performed using either an adult or pediatric colonoscope, or an upper endoscope for lesions within reach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation